ANALISIS PERAN BANK PERKREDITAN RAKYAT (BPR) TERHADAP PENINGKATAN KINERJA USAHA MIKRO KECIL (UMK) - Indria Widyastuti (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
Micro, Small and Medium Enterprises (SMEs) currently has a very big role towardseconomic development in Indonesia. SMEs also become the foundation for 99.45% oflabor in Indonesia.Various attempts were made by various parties to enhance the ability ofmicro, small and medium enterprises and cooperatives, one of which is the Rural Bank.Rural Bank role for communities in rural areas is expected to spearhead the MSE sector infinancing, by way of channeling credit to SMEs in the long run and do the coachingbusiness loans in order to improve the financial performance of SMEs receiving credit.Tosimplify the process of analysis undertaken, the author will make a model of analysis inorder to answer the problem. To prove the hypothesis presented in this study using simplelinear regression statistical tool with one independent variable (X) be the amount ofworking capital loans that have been disbursed by rural banks in West Java Province(specially in Bandung area) and three dependent variable (Y) in the form of increasedsales turnover, profit margins ratio and working capital turnover. Therefore, in this studywill use three simple regression equations models. Based on the results of regressionanalysis with the t-test on-year throughout the study period 2013-2015 found that: there isa positive influence among the independent variables are working capital loans disbursedRural Bank with an increase in the dependent variable.